Late Quaternary Palaeoclimate and Contemporary Moisture Source to Extreme NW India: A Review on Present Understanding and Future Perspectives - Sharma, Anupam; Phartiyal, Binita (Frontiers in Earth Science, 2018)
The trans-Himalayan region of NW India including the western part of Tibet, Karakoram, and Hindukush range host thousands of glaciers ensuring perennial freshwater supply to the Indian subcontinent and supports a large fraction of the global population. The peculiar physiography not only limits the entry of water enriched Indian Summer Monsoon winds to this region but also give passage to dry winds of barren desert of the Taklamakan, the Aksai Chin, and western Tibet, to qualify it as a cold desert. The Himalayan Orogen linked structural elements and the Quaternary glacial, and interglacial phases define the geomorphological setup of the region, which subsequently modified by the fluvial-lacustrine-aeolian processes. Over the years, our understanding in drawing climatic inferences from the sedimentary archives has improved significantly but the discrepancy in chronology, among and within different dating techniques, poses a serious challenge and therefore requires more work to address the issues. Similarly, till recently, it was argued that the major source of moisture to the Ladakh region is contributed from the Mediterranean Sea because the region falls under the rain shadow zone for the water-laden Indian summer monsoon winds. Our recent water isotopic study of upper Indus River Basin, however, emphasized that Indian summer monsoon source is also an equally important supplier. The present review highlights that the disturbed chronology and inadequate data support on moisture sources are two gap areas for further research.